Firefly Algorithm For Optimizing Single Axis Solar Tracker - Melfazen, Oktriza; Alawity, M. Taqijuddin; Dewatama, Denda (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2021)
Solar cells mounted on solar panel modules are expected to track sunlight throughout the day to produce maximum energy. The Firefly algorithm (FA) is embedded in the Arduino Mega microcontroller to control the tracking of the sun's position by the solar panel so that the absorption of solar energy can be as much as possible to get maximum electrical energy. The brightest light captured by the solar panel is represented as the light intensity of a firefly. The output of the solar tracking system is obtained by finding the best value of light intensity between fireflies. Parameter changes in FA, such as firefly population, random numbers, and number of iterations affect the results of FA. The largest population, the highest random number and iteration provide the best solution but take a long time to execute. FA can control solar panels in tracking the sun's position precisely with an average error of 1.28% and can absorb a total energy of 666.14 Watt/day. The best solution (98% of setpoint 720) was obtained when the population was set to 50, the random number to 0.8, and iteration to 50. This research can be used as a reference for later using a controller with higher specifications to speed up the FA process time in getting maximum control results.